2017
DOI: 10.1016/j.icarus.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Survival of fossilised diatoms and forams in hypervelocity impacts with peak shock pressures in the 1–19 GPa range

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…, above that for tardigrade survival. Separately, the peak shock pressures for terrestrial material impacting the Moon have been calculated for a range of possible impactor and lunar surface material combinations, and shock pressures were found to be in the range of 2–5 GPa (Burchell et al, 2017 ), which is consistent with those of Armstrong ( 2010 ), who pointed out, nonetheless, that 43% of impacts of terrestrial ejecta onto the lunar surface would be at speeds below 1 km s −1 . Indeed, 29% of such impacts have a vertical impact speed of less than 0.5 km s −1 , and 10% at less than 0.1 km s −1 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…, above that for tardigrade survival. Separately, the peak shock pressures for terrestrial material impacting the Moon have been calculated for a range of possible impactor and lunar surface material combinations, and shock pressures were found to be in the range of 2–5 GPa (Burchell et al, 2017 ), which is consistent with those of Armstrong ( 2010 ), who pointed out, nonetheless, that 43% of impacts of terrestrial ejecta onto the lunar surface would be at speeds below 1 km s −1 . Indeed, 29% of such impacts have a vertical impact speed of less than 0.5 km s −1 , and 10% at less than 0.1 km s −1 .…”
Section: Discussionsupporting
confidence: 70%
“…It has long been proposed that ejecta (and fossilized material within) from giant impacts on Earth could have struck the Moon and become preserved (Armstrong et al ., 2002 ; Armstrong, 2010 ; Burchell et al ., 2014 , 2017 ). Armstrong ( 2010 ) determined an average lunar impact speed for terrestrial ejecta of some 2.5 km s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…An experimental confirmation of the survival of biogenic material during impact was published by Burchell et al. (, ).…”
Section: Introductionmentioning
confidence: 66%
“…These data have shown that organic materials can survive capture and transportation by impact melt at impact processes. An experimental confirmation of the survival of biogenic material during impact was published by Burchell et al (2014Burchell et al ( , 2017.…”
Section: Introductionmentioning
confidence: 69%
“…If these were carried in frozen droplets in the plumes of an IOW, we can ask if they would be detectable after an impact on a passing spacecraft. This has been considered experimentally for diatoms and foraminifera (see Burchell, McDermott, et al., 2014; Burchell et al., 2017). It was found that, when embedded in ice projectiles (and the foraminifera were also suspended in water during shots), recognizable fossilized diatom and foraminifer structures survived in impacts at speeds up to 6 km s −1 (pressures of 20 GPa).…”
Section: Impact Shock‐induced Changes To Impactorsmentioning
confidence: 99%